The impact of the modified Atkins diet on lipid profiles in adults with epilepsy. (15th March 2016) - Cervenka, Mackenzie C.; Patton, Katlyn; Eloyan, Ani; Henry, Bobbie; Kossoff, Eric H.
Abstract : Objectives : The modified Atkins diet (MAD) is a high fat, low carbohydrate ketogenic diet used to treat intractable seizures in children and adults. The long-term impact on fasting lipid profiles (FLPs) remains unknown. This study was designed to detect significant lipid changes in adults on MAD. Methods : Patients were observed prospectively. A FLP was obtained in all patients at the first visit then serially. Patients were started on a 20 g per day net carbohydrate limit MAD. They were screened for risk for coronary heart disease and counseled to reduce saturated fats by a registered dietitian if deemed at risk. Patients that remained on MAD for 3 or more months with one or more follow-up FLP were included. Results : Thirty-seven patients (14 male), mean age 33 years (SD 13, range 18–59) met study criteria. Median diet duration was 16 months (range 3–41). Total cholesterol and low-density lipoprotein (LDL) increased significantly over the first 3 months of MAD ( P = 0.01 and 0.008, respectively), but were not significantly different from baseline after 1 year of treatment ( P = 0.2 and P = 0.5, respectively). High-density lipoprotein levels trended upward in the first 3 months ( P = 0.05) and triglycerides remained unchanged ( P = 0.5). In 12 patients followed for 3 or more years, no cardiovascular or cerebrovascular events were reported. Discussion : Although total cholesterol and LDL increased over the first 3 months of the MAD, these values normalized within a year of treatment, including in patients treated with MAD for more than 3 years.